Development‐based revision of bone tissue classification: the importance of semantics for science. (August 2014) - Prondvai, Edina; Stein, Koen H. W.; de Ricqlès, Armand; Cubo, Jorge
<x xml:space="preserve">Abstract</x> Research on the bone histology of extant and extinct animals has a long scientific history and an accurate description of microstructural tissues is the cornerstone of the field. Ideally, terminology needs to convey as much information as possible about the structural, developmental, and functional aspects of bone tissues corresponding to the up‐to‐date knowledge of the time. However, current terms are not always consistent with new observations and advances in the field of bone biology. We provide a brief overview of some ambiguities and their origins, and suggest a new approach of bone tissue classification and description that is congruent with our current understanding of bone as a living tissue, emphasizing its developmental aspects. This approach requires the introduction of a new term, namely 'woven‐parallel complex', for describing a broad range of complex bone tissue types, including intramembranous and endochondral bones, and different types of primary as well as secondary bone tissues. We reconsider the classical concept of fibrolamellar complex, which we place within the new developmental approach. Finally, using non‐archosaurian archosauromorphs as an example group, we demonstrate how the new approach can be utilized in an evolutionary context. The present study demonstrates the relevance and constant evolution of technical terminology along with the advances of the field of science. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 799–816.